RONALD DWORKIN â€“ THEORY OF JUSTICE - Vujadinovic, Dragica (European Scientific Journal, ESJ, 2012)
Ronald Dworkin - one of the greatest contemporary political and legal philosophers - started developing his comprehensive liberal theory of a central position of the concept of equality firstly in a field of philosophy of law1 (he turned back to a field of jurisprudence with his book Justice in Robes, published in 2006), then followed liberal political theory of justice/political morality (based on â€œequality of resourcesâ€ account of justice2), and finally he attempted to clarify philosophical foundations3 of this theory of political morality. His last book Justice for Hedgehogs4 has had an ambition to complete philosophical foundations of his theory, and especially to illustrate a unity of ethical and moral values. Dworkin has developed his theory of justice in a referental framewok of liberal theoretical attempts â€“ initiated by John Rawls in the 70s of the XX century â€“ to redeem political philosophy and theory of justice, in order that political legitimacy of liberal political and economic order be reconsidered and rearticulated as based on justice, i.e. just redistribution of reources. Â»Equality of resourcesÂ« account of justice represents a central point of Dworkin`s attempt to present egalitarian face of liberalism, to defend unity of values of equality and liberty, and to affirm value of equality as the central value of liberalism. He wants to keep individualism and value of liberty as an essence of liberalism, but also wants to demonstrate that equality has been even prior value in relation to liberty, that value of equality has been embeded in individuals and their interrelations through basic principles of humanism â€“ equal concern/respect for the human life as such and special responsibility of each individual for his/her own life. He wants to approve that justice has been a sovereign virtue of a political power, as well as that individuals do not have only egoistic interests, but have been inherently also committed to a common good; that justice represents a parameter also of individual ethics; that there exists continuity (Â»strategy of continuityÂ«) between pluralism of individual value orientations and common sharing of basic principles of humanism, between individualism and common good, between pluralism and neutrality of the state. This article will be primarily focused on Dworkin’s theory of justice, called Â»equality of resourcesÂ« account of justice, because, firstly, it is a central focus of Dworkin`s still being produced and productive theoretical legacy; secondly, it represents a very complex theoretical endeavour which needs to be particularly analized; and, thirdly, Dworkin`s conception of law (law as integrity) and of morality (philosophical foundations of his theory of justiice), as well as his specific conception of liberalism (Â»liberal equalityÂ«) cannot be fully understood without understanding his Â»equality of resourcesÂ« account of justice.